Optogenetic Protein Cleavage in Zebrafish Embryos. (9th November 2022) - Brown, Wes; Albright, Savannah; Tsang, Michael; Deiters, Alexander
Abstract: A wide array of optogenetic tools are available that allow for precise spatiotemporal control over cellular processes. These tools are particularly important to zebrafish researchers who take advantage of the embryo's transparency. However, photocleavable optogenetic proteins have not been utilized in zebrafish. We demonstrate successful optical control of protein cleavage in embryos using PhoCl, a photocleavable fluorescent protein. This optogenetic tool offers temporal and spatial control over protein cleavage events, which we demonstrate in light‐triggered protein translocation and light‐triggered apoptosis. Abstract : Optical control of nuclear translocation and activation of apoptosis in zebrafish embryos was demonstrated by using a photocleavable fluorescent protein. Rapid and precise activation of caspase‐3 was observed in cells irradiated with a short pulse of a confocal microscope 405 nm laser.